Electron donor addition for stimulating the microbial degradation of 1, 4 dioxane by sequential batch membrane bioreactor: A techno-economic approach. (November 2022) - Tawfik, Ahmed; Al-sayed, Aly; Hassan, Gamal K.; Nasr, Mahmoud; El-Shafai, Saber A.; Alhajeri, Nawaf S.; Khan, Mohd Shariq; Akhtar, Muhammad Saeed; Ahmad, Zubair; Rojas, Patricia; Sanz, Jose L.
Abstract: The presence of 1, 4 dioxane in wastewater is associated with severe health and environmental issues. The removal of this toxic contaminant from the industrial effluents prior to final disposal is necessary. The study comprehensively evaluates the performance of sequential batch membrane bioreactor (MBR) for treating wastewater laden with 1, 4 dioxane. Acetate was supplemented to the wastewater feed as an electron donor for enhancing and stimulating the microbial growing activities towards the degradation of 1, 4 dioxane. The removal efficiency of 1, 4 dioxane was maximized to 87.5 ± 6.8% using an acetate to dioxane (A/D) ratio of 4.0, which was substantially dropped to 31.06 ± 3.7% without acetate addition. Ethylene glycol, glyoxylic acid, glycolic acid, and oxalic acid were the main metabolites of 1, 4 dioxane biodegradation using mixed culture bacteria. The 1, 4 dioxane degrading bacteria, particularly the genus of Acinetobacter, were promoted to 92% at the A/D ratio of 4.0. This condition encouraged as well the increase of the main 1, 4 dioxane degraders, i.e., Xanthomonadales (12.5%) and Pseudomonadales (9.1%). However, 50% of the Sphingobacteriales and 82.5% of Planctomycetes were reduced due to the inhibition effect of the 1, 4 dioxane contaminate. Similarly, the relative abundance of Firmicutes, Verrucomicrobia, Chlamydiae, Actinobacteria, Chloroflexi, and Nitrospirae was reduced in the MBR at the A/D ratio of 4.0. The results derived from the microbial analysis and metabolites detection at different A/D ratios indicated that acetate supplementation (as an electron donor) maintained an essential role in encouraging the microorganisms to produce the monooxygenase enzymes responsible for the biodegradation process. Economic feasibility of such a MBR system showed that for a designed flow rate of 30 m 3 ∙d −1, the payback period from reusing the treated wastewater would reach 6.6 yr. The results strongly recommend the utilization of mixed culture bacteria growing on acetate for removing 1, 4 dioxane from the wastewater industry, achieving dual environmental and economic benefits. Graphical abstract: Image 1 Highlights: Sequential batch membrane bioreactor is efficient for 1, 4 dioxane biodegradation. The removal of 1, 4 dioxane amounted to 87.5 ± 6.8% at acetate to 1, 4 dioxane ratio of 4.0 Proteobacteria phyla were increased from 30.1 to 69.5% and Rhodobacterales from 0.3 to 19%. Xanthomonadales were boosted from 0.9 to 12.5% with 1, 4 dioxane addition. Acinetobacter genus degrading 1, 4 dioxane accounted for 92% of the Pseudomonadales .